Assessing Atherosclerotic Cardiovascular Disease Risk with Advanced Lipid Testing: State of the Science - Charles Amir German; Michael David Shapiro (European Cardiology Review)
Cardiovascular disease is the number one cause of death and disability worldwide. While substantial gains have been made in reducing cardiovascular mortality, future projections suggest that we have reached a nadir and may be at an inflection point, given the rising tide of obesity and diabetes. Evaluation and management of plasma lipids is central to the prevention of atherosclerotic cardiovascular disease. Although the standard lipid panel represents a well-established platform to assess risk, this test alone can be insufficient and/or misleading. Advances in our understanding of atherosclerosis have led to the development of lipid-based biomarkers that help to discriminate the risk of cardiovascular disease when it is unclear. While these biomarkers provide novel information, their implementation into clinical medicine remains difficult given discrepancies in the literature, lack of assay standardisation, poor accessibility and high cost. However, additional measures of atherogenic lipoproteins or their surrogates may offer insight beyond the standard lipid panel, providing a more precise assessment of risk and more accurate assessment of lipid-lowering therapy.